UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MULTIMEDIA INTERAKTIF - Rahmi Hayati; Dian Armanto; Zuraini Zuraini (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The most pressing issue at SD Negeri 4 Bireuen is the school's inability to effectively address student and teacher concerns.This study aims to improve teachers' problem-solving skills. This study employs a qualitatve approach. Research participants include 36 third-year students from SD Negeri 4 Bireuen. This study's information was gathered by means of a questionnaire, participant observations, and key informant interviews. This study employs a descriptive data analysis method. The implementation of the Problem-Based Learning pedagogical approach has the potential to improve students' problem-solving abilities in the area of statistics, specifically in the areas of sample size determination and reduction, in the third grade of SD Negeri 4 Bireuen. This is evidenced by the fact that student problem-solving abilities increased from 82.3 percent in the first semester to 94.1 percent in the second. Utilizing interactive video can help students' attention during the learning process and can help students develop a sense of satisfaction from their studies. There have been comments from users who have affirmed the validity and value of interactive video. This is due to the fact that educational media has become more valuable as a result of the integration of previously unreliable components.